Signal-detection properties of verbal self-reports. - Critchfield, T S (1993)
The bias (B'H) and discriminability (A') of college students' self-reports about choices made in a delayed identity matching-to-sample task were studied as a function of characteristics of the response about which they reported. Each matching-to-sample trial consisted of two, three, or four simultaneously presented sample stimuli, a 1-s retention interval, and two, three, or four comparison stimuli. One sample stimulus was always reproduced among the comparisons, and choice of the matching comparison in less than 800 ms produced points worth chances in a drawing for money. After each choice, subjects pressed either a "yes" or a "no" button to answer a computer-generated query about whether the choice met the point contingency. The number of sample and comparison stimuli was manipulated across experimental conditions. Rates of successful matching-to-sample choices were negatively correlated with the number of matching-to-sample stimuli, regardless of whether samples or comparisons were manipulated. As in previous studies, subjects exhibited a pronounced bias for reporting successful responses. Self-report bias tended to become less pronounced as matching-to-sample success became less frequent, an outcome consistent with signal-frequency effects in psychophysical research. The bias was also resistant to change, suggesting influences other than signal frequency that remain to be identified. Self-report discriminability tended to decrease with the number of sample stimuli and increase with the number of comparison stimuli, an effect not attributable to differential effects of the two manipulations on matching-to-sample performance. Overall, bias and discriminability indices revealed effects that were not evident in self-report accuracy scores. The results indicate that analyses based on signal-detection theory can improve the description of correspondence between self-reports and their referents and thus contribute to the identification of environmental sources of control over verbal self-reports.